2014
DOI: 10.2174/1567205011666140131114418
|View full text |Cite
|
Sign up to set email alerts
|

Retinal Nerve Fiber Layer Thickness is Associated with Episodic Memory Deficit in Mild Cognitive Impairment Patients

Abstract: Changes in retinal nerve fiber layer (RNFL) thickness have been reported in patients with mild cognitive impairment (MCI), the pre-dementia stage of Alzheimer's disease (AD). However, whether RNFL thickness is associated with specific cognitive impairment of MCI patients remains unknown. Therefore, we set out to investigate the potential association between RNFL thickness and episodic memory in MCI patients. Seventy five older adults (mean age 74 ± 3 years, 55% men) were included in the study. Fifty-two partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 0 publications
2
61
1
Order By: Relevance
“…A recent study has found significant reduction of RNFL thickness in AD patients compared to healthy individuals (14). The result of a current study suggested that RNFL could serve as a biomarker of mild cognitive impairment and AD (15).…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…A recent study has found significant reduction of RNFL thickness in AD patients compared to healthy individuals (14). The result of a current study suggested that RNFL could serve as a biomarker of mild cognitive impairment and AD (15).…”
Section: Discussionsupporting
confidence: 58%
“…Recent OCT studies have described a loss of the RNFL thickness in patients with AD (9)(10)(11)(12)(13)(14)(15).…”
mentioning
confidence: 99%
“…Other studies have shown a significant correlation between RNFL thickness and MMSE scores in patients with MCI and AD 86 and RNFL thickness has been significantly associated with other cognitive domains including reaction times. 87 However, the findings are not universal: both an inverse association 88 and no association 89 between RNFL and cognitive test scores have been reported. A large-scale population-based study 90 showed that better cognitive performance was significantly associated with a thicker RNFL (r 2 = 0.028, P = 0.03) in healthy young individuals without any cognitive impairment, but there were no significant associations found in older participants.…”
Section: The Rnfl In Admentioning
confidence: 97%
“…Several studies have used OCT to examine the RNFL in subjects with a clinical diagnosis of MCI [17–26]. Ascaso et al.…”
Section: Introductionmentioning
confidence: 99%